Consumer Purchasing Process in Digital Market: A Case Study of Small and Medium Enterprises in Thailand - Praditsuwan, Nattaya; Karnreungsiri, Isaree (Asian Administration and Management Review, 2019)
Most marketers have accepted that digital marketing provides Small and Medium Enterprises (SMEs) many benefits. It enables SMEs to develop and implement suitable marketing strategies in a more meaningful way to serve consumers demand in the digital era. Many researchers have widely studied consumer purchasing process in the digital market. Nevertheless, there are limited papers reviewed on the relationship between the purchasing process and the consumer’s decision of the SMEs consumers. Thus, this paper was intended to explore this relationship in term of the impact which the purchasing process has on the consumer’s decision. Exploratory Factor Analysis (EFA) and Cronbach’s Alpha were applied to test the validity and reliability of the data gathered from 400 respondents with a selfadministered questionnaire. In this study, the authors employed inferential statistics analysis by Multiple Regression Model to conduct a hypothesis test. The result showed that the variables under only four stages of purchasing process which significantly impacted on the consumer’s decision were media, supplier, interaction, trustworthiness, website, recognition, integrity, prominence, distinction, procedure, and complaint. The finding was useful for the SMEs entrepreneurs in developing marketing strategies to cope with consumer behavior under a sophisticated digital market.